Biodegradation of NR Latex-based Materials via a Carbon Dioxide Evolution Method - F. M. S. Shabinah; M. Y. A. Hashim (Universitas Gadjah Mada, 2013)
NR as a natural polymer has biodegradable characteristics and their existence was examined using CO2 evolution methods. The CO2 molecule produced by micro-organism metabolisms in the degradation system was quantified using a conventional acidimetric method. An aerobic system was determined as most suitable condition to be examined under this method. The presence of O2 in the system would help micro-organisms to destabilize the natural polymer. The material of LATZ, HA film and NR gloves showed significant weight loss and were able to produce CO2 evolution curves after 45 days in the biodegradation system compared to synthetic polyisoprene films. Gel permeation chromatography, fourier transform infrared spectroscopy and scanning electron micrograph were used to characterize the degraded sample at molecular and physical levels.